Evodio de Uzalis y el desarrollo del maniqueísmo en la provincia romana del norte de África - Vanspauwen, Aäron (Avgvstinvs, 2024)
This article examines part of the development of North African Manichaeism, with a specific focus on Aduersus Manichaeos, an anti-Manichaean tretaise attributed to Evodius of Uzalis. Evodius, a friend of Augustine of Hippo, probably wrote Aduersus Manichaeos in the years 425. The treatise constitutes an important source on North African Manichaeism, written two decades after the major anti-Manichaean works of Augustine. A preliminary section discusses Evodius' sources. Unlike Augustine he was not a former member of the Manichaean movement, and his Adversus Manichaeos lacks the insiders' knowledge of Augustine's treatises. Nevertheless, it will be argued that Evodius had prepared himself thoroughly in order to write his anti-Manichaean treatise. The subsequent section offers an overview of testimonia on the Manichaean canon in the Latin world. These testimonia seem to suggest - that over time - the North African Manichaeans held one particular letter of Mani, the Epistula Fundamenti, in high esteem. The concluding section briefly addresses the genre, status, contents and circulation of Mani's letter.